Cross-Sectional Imaging and Risk Factors Associated with Stroke Features - Rowa Mahmoud Aljondi; Waad Saad Alharthi; Samaher Mohammed Alyanbaawi; Abdulrzzag Abdulkarim Alghamdi; Salem Saeed Alghamdi; Abdulrahman Tajaldeen (International Journal of Biomedicine)
Background: Among health problems that can damage the brain, stroke is one of the most dangerous. However, there is relatively little information on the risk factors related to stroke in Saudi Arabia, especially in Jeddah. This study aims to identify stroke features on cross-sectional imaging and stroke-associated risk factors in Jeddah, Saudi Arabia. Methods and Results: This retrospective study included 131 patients admitted to governmental institutions (King Abdulaziz Hospital and East Jeddah Hospital) from 2017 to 2022. The present study included only patients with a brain CT scan without a contrast agent. MRI (1.5 Tesla) was considered for follow-up patients. Most of the stroke patients were over age 60 (66.4%). The distribution of stroke patients showed a higher percentage of males compared to females (59.5% versus 40.5%) (P=0.029). The most frequent attributable risk for stroke was found in 36 patients, of which 24 (66.7%) had hypertension, 22 (61.1%) - diabetes mellitus, 14 (38.9%) - previous stroke, and 6 (16.7%) had coronary heart disease. The majority of patients (85.5%) were diagnosed with ischemic stroke, and 11.5% had hemorrhagic stroke. Ischemic stroke was significantly associated with diabetes (100.0% versus 82.6% in nondiabetics) (P=0.042). The most common stroke site was intracranial (lobar) infarction (32.1%), followed by a middle cerebral artery (MCA) stroke (21.4%). Conclusion: The study findings indicated that the males exhibited a higher stroke incidence rate than the females. The major type of stroke was ischemic stroke. Hypertension and diabetes mellitus are the most common vascular risk factors for stroke. Early controlling vascular risk factors could help prevent stroke at an older age.